On the prediction of non‐linear creep strains - Balevičius, Robertas; Dulinskas, Eugedijus (Journal of Civil Engineering and Management, 2010)
In the short term, the Euorocode‐based techniques will be implemented as the main design specifications for structural engineers from the member‐states of the European Union instead of the national standards. Therefore, it is of primary importance draw attention to the observed inaccuracies, particularly, in predicting non‐linear creep strains according to EC‐2. The analysis performed was mainly focused on an inconsistency elimination observed in the original EC‐2 approach, when transition from the linear to non‐linear creep laws for a constant compressive stress is required. A recent CEN corrigendum eliminating the observed inconsistency was also discussed in detail.  In this context, similar techniques which were reported in the literature for predicting the creep non‐linearity function were analysed to account for the results obtained. It was particularly demonstrated that the recent CEN amendment results in an extremely enhanced creep strain for low strength concrete. A comparison of the creep non‐linearity functions with experimental test results was also considered.First Published Online: 10 Feb 2011